Perfectly Present: Mindfulness Curriculum as Implicit Religion. (1st March 2018) - Hale, Mary
Abstract : Mindfulness has become increasingly popular in western education: both as a pedagogical term and as a curriculum tool. Although promoters, with varying degrees of emphasis, claim that mindfulness in this context is non-religious, this paper challenges those assertions. Using Charles Taylor's arguments regarding belief and unbelief and his conception of fullness and Edward Bailey's conception of implicit religion, I contend that mindfulness as curriculum or as curriculum enrichment is a form of implicit religion.